(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Very limited studies of nurse turnover have been conducted in spite of rising rates of turnover, especially in private and trust-based hospitals. The object of this the study is to conduct an empirical study of the causes and consequences of nursing turnover in a trust-based hospital. In this study, essential information (Primary data) was gathered to search the exact reasons behind turnover and its subsequent outcome; notwithstanding that the researcher also accumulated secondary data to ascertain the precise causes of turnover. To investigate the causes and its subsequent results of nurse turnover, all hypotheses are tested by the statistical (kruskal Wallis test) process. Nurse, Turnover, Workload, Job-Satisfaction, Conflict, Workflow, Increased-Cost, Stress and Patient- Flow: